Sistema Web de gestión y seguimiento de las Convocatorias internas de proyectos I+D+i de la ESPAM MFL - Cedeño Reyes, María Bélen (2018)
Based on the thesis objective, a web management and follow-up system called by their authors as “PROGIDI”, was developed for the internal convocatory of I+D+i projects, in response to the needs of the Scientific Research Coordination of ESPAM MFL, which aims to streamline processes that are given in all the stages existing within a project convocatory, that is to say improving the interaction between the CIC and the researchers, the presentation of the semi-annual and annual reports, and others. The system was developed based on the SCRUM methodology, which in the first stage allowed the planning of the developed of the main system requirements previously established in the ERS sheet of the IEEE-830 standard, in addition to the tools to be implemented, which were ASP.net (Visual Studio 2015) as a developed platform, SQL 2012 as Database Manager; all this in an architecture of three layers, then in the second stage, the development results of each of the requirements are documented, which results a history of the Product Backlog (system) development; finally, the third stage of evaluation and delivery of the final product was given, where the idea to be defended is also supported. The results obtained in this last stage have shown a significant improvement in the management and monitoring of the I+D+i projects, which has led to the conclusion that the system has optimized the execution time of specific tasks up to 99.85%.